Presymptomatic spinal cord pathology in c9orf72 mutation carriers: A longitudinal neuroimaging study - Querin, Giorgia; Bede, Peter; El Mendili, Mohamed Mounir; Li, Menghan; Pélégrini‐Issac, Mélanie; Rinaldi, Daisy; Catala, Martin; Saracino, Dario; Salachas, François; Camuzat, Agnes; Marchand‐Pauvert, Véronique; Cohen‐Adad, Julien; et al. (Annals of neurology, 2019)
Objective C9orf72 hexanucleotide repeats expansions account for almost half of familial amyotrophic lateral sclerosis (ALS) and frontotemporal dementia (FTD) cases. Recent imaging studies in asymptomatic C9orf72 carriers have demonstrated cerebral white (WM) and gray matter (GM) degeneration before the age of 40 years. The objective of this study was to characterize cervical spinal cord (SC) changes in asymptomatic C9orf72 hexanucleotide carriers. Methods Seventy‐two asymptomatic individuals were enrolled in a prospective study of first‐degree relatives of ALS and FTD patients carrying the c9orf72 hexanucleotide expansion. Forty of them carried the pathogenic mutation (C9+). Each subject underwent quantitative cervical cord imaging. Structural GM and WM metrics and diffusivity parameters were evaluated at baseline and 18 months later. Data were analyzed in C9+ and C9− subgroups, and C9+ subjects were further stratified by age. Results At baseline, significant WM atrophy was detected at each cervical vertebral level in C9+ subjects older than 40 years without associated changes in GM and diffusion tensor imaging parameters. At 18‐month follow‐up, WM atrophy was accompanied by significant corticospinal tract (CST) fractional anisotropy (FA) reductions. Intriguingly, asymptomatic C9+ subjects older than 40 years with family history of ALS (as opposed to FTD) also exhibited significant CST FA reduction at baseline. Interpretation Cervical SC imaging detects WM atrophy exclusively in C9+ subjects older than 40 years, and progressive CST FA reductions can be identified on 18‐month follow‐up. Cervical SC magnetic resonance imaging readily captures presymptomatic pathological changes and disease propagation in c9orf72‐associated conditions. ANN NEUROL 2019;86:158–167